FOOD MICROBIOLOGY AND FOOD SAFETY: THE JOURNEY OF SAFE FOOD (Editora Impacto Científico, 2025)
Food safety is a pillar of public health, but the occurrence of Foodborne Illnesses (FBIs) shows that legal compliance doesn't always guarantee food safety. Food microbiology is an essential tool for identifying invisible hazards, as failures in Good Manufacturing Practices (GMPs), transport, and storage can compromise product quality, even in those that meet ANVISA standards. In-depth knowledge of microorganisms and their response to factors like temperature is crucial for implementing strict controls. Beyond official regulations, professional qualification and continuing education are fundamental. The practical application of microbiology and the use of preventive systems like HACCP are the nutritionist's greatest contribution to ensuring food is safe at every link in the chain, thereby protecting consumer health.DOI: https://doi.org/10.56238/edimpacto2025.090-011